Experimental investigation on the flexural behavior of steel-concrete composite beams with U-shaped steel girders and angle connectors. (15th January 2017) - Liu, Yong; Guo, Lanhui; Qu, Bing; Zhang, Sumei
Highlights: Five composite beams with U-shaped steel girder and angle connectors were tested. Fully composite beams exhibit great ductility. The formula for channel connectors cannot be used to design angel connectors. Provisions in EC4 can be used for computing strength of the composite beams in this study. The cracked moment of inertia should be used to predict the initial stiffness of composite beams. Abstract: This paper focuses on a new type of steel-concrete composite beams consisting of U-shaped steel girders and angle connectors. Compared with conventional steel-concrete composite beams consisting of wide flange girders and headed shear stud connectors (or short channel connectors), the composite beams considered in this study have favorable flexural performance while reducing the excessive costs and potential construction challenges due to installation of the stud and/or channel shear connectors. Through four-point bending tests on five specimens, this research team experimentally investigated flexural behavior of the new composite beams. The five specimens were varied to have different angle connector intervals and installation locations. Test results show that composite beams with angle connectors welded to the webs of U-shaped steel girder fail in brittle failure modes while composite beam with angle connectors welded on the top flange of U-shaped steel girder fails in ductile failure mode. Based on the test results, it can be concluded that angle connectors welded on the top flange are more ductile than those welded to the webs. This paper also assesses adequacy of the existing formula for short channel connectors in quantifying the shear transfer capacity of angle connectors and the influence of installation location of angle connectors on the resulting beam response. Moreover, plastic moment resistance of the composite beam with full shear connection predicted by Eurocode 4 and AISC 360 and ultimate flexural strength of the partially composite beams predicted by the interpolation method in Eurocode 4 agree well with the experimental results. Besides, specifications in AS 2327.1 and provisions in AISC 360 neglecting the reduction factor could be used to estimate the initial stiffness of composite beams in this study by using cracked moment of inertia.